2015
DOI: 10.1007/s00428-015-1778-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle and apoptosis regulatory proteins, proliferative markers, cell signaling molecules, CD209, and decorin immunoreactivity in low-grade myxofibrosarcoma and myxoma

Abstract: The histologic differential diagnosis between intramuscular myxoma and low-grade myxofibrosarcoma can be quite difficult in some cases. To identify a diagnostic immunohistochemical marker, we compared the staining profiles of 19 different antigens, including cell cycle proteins, apoptosis proteins, and proliferative markers, and selected other signaling and structural proteins in these two tumors. Ten cases each of intramuscular myxoma and low-grade myxofibrosarcoma were stained with antibodies directed agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In a recent study, on the other hand, Cates et al [28] saw no difference in decorin immunoreactivity between myxoma and myxofibrosarcoma. In fact, none of the 19 potential diagnostic markers tested distinguished myxoma from myxofibrosarcoma [28]. The authors concluded that the distinction between these tumors must still be made based on morphologic criteria.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a recent study, on the other hand, Cates et al [28] saw no difference in decorin immunoreactivity between myxoma and myxofibrosarcoma. In fact, none of the 19 potential diagnostic markers tested distinguished myxoma from myxofibrosarcoma [28]. The authors concluded that the distinction between these tumors must still be made based on morphologic criteria.…”
Section: Discussionmentioning
confidence: 90%
“…Both decorin immunoreactivity and mRNA expression of DCN (the gene coding for decorin) were positive in the former but not in the latter [27]. In a recent study, on the other hand, Cates et al [28] saw no difference in decorin immunoreactivity between myxoma and myxofibrosarcoma. In fact, none of the 19 potential diagnostic markers tested distinguished myxoma from myxofibrosarcoma [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that GMNN is associated with different diseases including cancer. GMNN have been found to associate with regulation of apoptosis, regulatory proteins of cell cycle, cell proliferation markers, signaling molecules and extracellular matrix moieties [3]. Proliferation and labeling index are the two parameters that are used to measure dividing cells in particular tumor and mitotic activity of a cell population respectively.…”
Section: Editorialmentioning
confidence: 99%
“…Benign myxoid tumors include myxomas and angiomyxomas; and malignant myxoid tumors include fibromyxoid sarcomas, extraskeletal myxoid chondrosarcomas, ossifying fibromyxoid tumors, myxoid liposarcomas, myxoinflammatory fibroblastic tumors and myxofibrosarcomas [1]. Each myxoid neoplasms has key chromosomal translocations or immunohistochemical markers that are pathognomic for its diagnosis except for myxomas and myxofibrosarcomas [18]. Myxofibrosarcomas and myxomas are not associated with any particular translocation or gene expression product, and their diagnoses are based on their histological appearances [1, 810].…”
Section: Introductionmentioning
confidence: 99%
“…Each myxoid neoplasms has key chromosomal translocations or immunohistochemical markers that are pathognomic for its diagnosis except for myxomas and myxofibrosarcomas [18]. Myxofibrosarcomas and myxomas are not associated with any particular translocation or gene expression product, and their diagnoses are based on their histological appearances [1, 810]. Therefore, one of the greatest diagnostic dilemmas for a pathologist lies in differentiating a myxoma from a myxofibrosarcoma, and particularly differentiating a cellular myxoma from some low-grade myxofibrosarcomas [1, 810].…”
Section: Introductionmentioning
confidence: 99%